2016
DOI: 10.1002/jssc.201600180
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography with mass spectrometry for the quantification of ethylene glycol ethers in different household cleaning products

Abstract: A rapid and simple procedure is reported for the determination of six ethylene glycol ethers in cleaning products and detergents using gas chromatography with mass spectrometry. The analytes were extracted from 2.0 g samples in acetonitrile (3 mL) and the extract was submitted to a clean-up step by QuEChERS method, using a mixture containing 0.3 g magnesium sulfate, 0.15 g primary/secondary amine, and 0.05 g C18 . The clean acetonitrile extract (1 μL) was injected into the chromatographic system. No matrix eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The alcohol from which it is synthesized ( n -butanol) is partially soluble in water at room conditions, with an upper critical solubility temperature ( T = 403.1 K and a molar fraction of 0.1070). , The addition of an ethylene oxide (EO) molecule, as part of the hydrophilic region, dramatically changes its physical properties to a completely miscible solvent in water at room temperature and the phase diagram changes to a closed two-phase loop with an upper and lower critical solubility temperature (around 402.86 and 322.12 K for the upper and lower critical solution temperature, respectively). EO provides an important surface activity, making EGBE one of the smallest surfactants. EGBE application scope covers several uses: as a component in fracturing and drilling fluids for the petroleum industry, , as an additive in ink, lacquers, varnishes, and enamels in the painting industry, , and as a cosurfactant in cleaning products, among others. To predict its performance in such applications, it is important to know its physical properties, especially the surface tension behavior in aqueous systems.…”
Section: Introductionmentioning
confidence: 99%
“…The alcohol from which it is synthesized ( n -butanol) is partially soluble in water at room conditions, with an upper critical solubility temperature ( T = 403.1 K and a molar fraction of 0.1070). , The addition of an ethylene oxide (EO) molecule, as part of the hydrophilic region, dramatically changes its physical properties to a completely miscible solvent in water at room temperature and the phase diagram changes to a closed two-phase loop with an upper and lower critical solubility temperature (around 402.86 and 322.12 K for the upper and lower critical solution temperature, respectively). EO provides an important surface activity, making EGBE one of the smallest surfactants. EGBE application scope covers several uses: as a component in fracturing and drilling fluids for the petroleum industry, , as an additive in ink, lacquers, varnishes, and enamels in the painting industry, , and as a cosurfactant in cleaning products, among others. To predict its performance in such applications, it is important to know its physical properties, especially the surface tension behavior in aqueous systems.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, most of the reported methods for the determination of glycol ethers and their acetates were mainly based on GC , GC–MS , and HPLC–MS/MS . The analyzed samples in these studies were focused on environmental samples, leather products, foods, toys, textiles, and decorating and refurbishing materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, the method presents an LOQ of about 5 g/g and an LOD of about 1 g/g, which are high levels for detecting genotoxins in pharmaceuticals and unsuitable for use. In recent years, the use of MS for the quantitative analysis of trace-level impurities has increased [11,12]. Lee et al [13] reported a GC-MS method, wherein mesylate esters are derivatized with aqueous sodium thiocyanate.…”
Section: Introductionmentioning
confidence: 99%